Applying Lean Canvas in Social Enterprises: A Bibliometric Study - Amelia Dwi Marthasari; Nurul Asfiah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Social Business combines a social mission with business principles to create a positive impact on society while ensuring financial sustainability. Lean Canvas, a tool developed by Ash Maurya, has been recognized as an effective method for quickly designing and testing business models. This study aims to analyze research trends on the application of Lean Canvas in social business using a bibliometric approach. Data were collected from major academic databases such as Google Scholar. The analysis was conducted using VOSviewer and Bibliometrix software, covering annual publication trends, geographical distribution, the most productive authors, the most frequently cited articles, collaboration networks, and main research topics. The results of the analysis show a significant increase in the number of publications on Lean Canvas in social business over the past decade, with a peak in publications occurring in the last five years. Publications are distributed globally, with the highest concentrations in the United States, the United Kingdom, and India. Several authors stand out as the most productive and influential. Collaboration network analysis reveals close relationships between researchers from various institutions and countries, reflecting strong international collaboration. Major research topics include business innovation, social sustainability, social impact, and Lean methodology. Lean Canvas has become an essential tool in social business, with increasing attention from researchers and practitioners. This bibliometric analysis provides deep insights into the trends, influence, and collaboration networks in this research area, and identifies the main topics that researchers focus on. The results of this study are expected to aid in understanding the development and future direction of research on Lean Canvas in social business.